DIGITAL BRANDING STRATEGY OF @puncakstelingsamarinda IN PROMOTING PUNCAK STELING TOURISM - Putri Cahaya Ramadhani; Wulan Damaryam; Siti Salmah Nurhafsah; A. Rivai Beta (Universitas Islam Negeri Mataram, 2026)
This study is motivated by the increasing use of social media for tourism promotion in the digital era. Puncak Steling Tourism in Samarinda uses Instagram as a digital branding platform to introduce the destination to a wider public. This study employs a qualitative approach based on Chris Heuer’s 4C Social Media Theory. The results show that digital branding strategies are implemented through four dimensions: context, communication, collaboration, and connection. Among these dimensions, context emerges as the most dominant aspect in shaping the image of the tourism destination. This study concludes that Instagram effectively supports promotional activities and expands the dissemination of information about Puncak Steling Tourism in Samarinda.